Influence of precursor solution concentration on the structural, optical and humidity sensing properties of spray-deposited TiO2 thin films. (December 2018) - Gapale, Dipak L; Arote, Sandeep A; Palve, Balasaheb M; Borse, Ratan Y
Abstract: In the present paper, the influence of precursor concentration on the structural, optical, and humidity sensing properties of spray-deposited titanium dioxide (TiO2 ) films are investigated. The TiO2 thin films were successfully deposited by spraying different precursor concentrations such as 0.075 M, 0.1 M, and 0.125 M of titanium trichloride solution onto glass substrates. X-ray diffractometry (XRD) studies confirmed the polycrystalline anatase phase of TiO2 with dominant (101) plane. The crystallite size was found to increase with the increase in precursor concentration. The micro-strain and dislocation density in the film was observed to decrease as the crystallite size increased. The UV–vis spectra confirmed the optical absorbance edge of the samples shifted toward lower wavelengths with increased precursor concentration. The humidity sensing properties of the synthesized material were measured by monitoring the change in resistance of the sample with the change in relative humidity. The material synthesized with 0.1 M precursor concentration, by using the spray pyrolysis method, shows good sensitivity and has a response time of 77.5 s and fast recovery time of 3 s.